Androgens and the endometrium - Suri, Narinder K. (1988)
The role of C19 steroids in the human endometrium is at present unclear. In order to gain an insight into their action, radioimmunoassay procedures were developed which had sufficient specificity and accuracy to measure testosterone, 5α-DHT, oestradiol, progesterone and androstenedione in endometrial samples. Amounts of androstenedione were greater (range 1.2-20.8 ng/mg tissue) than other steroids. Samples were obtained from patients presenting with a variety of conditions: subfertility, postmenopausal bleeding, dysfunctional uterine bleeding and abdominal pain. Patients admitted for sterilisation were used as normal controls.